2016
DOI: 10.7203/attic.17.9097
|View full text |Cite
|
Sign up to set email alerts
|

Transforming a class from the Psychology degree into a <em>flipped classroom</em>

Abstract: ResumenLa flipped classroom es una metodología docente que trata de modificar la dinámica de la clase tradicional, en la que el alumnado estudia la materia antes de asistir a clase (fundamentalmente mediante Tecnologías de la Información y Comunicación), y el tiempo en el aula se emplea para clarificar contenidos y realizar actividades significativas, con el apoyo continuado del profesorado. Estudios recientes muestran que se han obtenido resultados positivos respecto a la utilización de esta metodología. Sin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(14 reference statements)
1
3
0
3
Order By: Relevance
“…Likewise, the fact of giving the students autonomy in carrying out the tasks [14] affects the development of creativity, as confirmed in this experience. Regarding the development of personal and communication skills, these are enhanced by teamwork that favours the Flipped Classroom [8,12,13], in the same way that the percentage of student agreement is 81.7% (social and personal skills) and 72% (teamwork).…”
Section: Discussionsupporting
confidence: 72%
“…Likewise, the fact of giving the students autonomy in carrying out the tasks [14] affects the development of creativity, as confirmed in this experience. Regarding the development of personal and communication skills, these are enhanced by teamwork that favours the Flipped Classroom [8,12,13], in the same way that the percentage of student agreement is 81.7% (social and personal skills) and 72% (teamwork).…”
Section: Discussionsupporting
confidence: 72%
“…In agreement with studies by earlier authors in which the flipped classroom method was applied (Alebrahim & Ku, 2020;Campos-Mesa, 2022;Zhu, Lian & Engström, 2020), what has been verified here is an improvement in academic performance on the module, in this case of almost one extra point on a ten-point scale when comparing the academic results obtained in the module's final exam between the students who participated in this experiment and those who did not. This can be attributed to an increase in hours dedicated to learning with increased daily effort and attention (Salcines-Talledo, Cifrián-Bemposta, González-Fernández & Viguri-Fuente, 2020), to the commitment and central role of the students (Miragall & García-Soriano, 2016) and to the fact that the teacher prepared videos explaining the topic and providing additional material for study, helping to involve students fully in the learning process.…”
Section: Discussionmentioning
confidence: 99%
“…Turan & Akdag-Cimen (2019), who conducted a review of flipped classroom approach in English language classrooms, also reported that the use of flipped classroom approach was workable especially for the speaking and writing skills. Nevertheless, although previous studies including by Andujar et al (2020) have indicated the benefits gained by students in a flipped classroom, studies conducted by Vuong (2018) and Miragall & García-Soriano (2016) have shown that students often face challenges in participating in the flipped classroom setting.…”
Section: Introductionmentioning
confidence: 93%